Development of antimicrobial films with cinnamaldehyde stabilized by ethyl lauroyl arginate and cellulose nanocrystals. (September 2022) - Zhang, Kailong; Ren, Tian; Harper, David; Li, Mi
Abstract: Antimicrobial films were developed by incorporating cellulose nanocrystals (CNC) and cinnamaldehyde-based Pickering emulsions into polyvinyl alcohol. The food-grade cationic surfactant, ethyl lauroyl arginate (LAE), was used to modify CNC for emulsion stability improvement. We contend that the LAE reduced the electrostatic repulsion by partially neutralizing the CNC surface charge and increased its packing density around the droplet interface. The CNC/LAE and cinnamaldehyde mixture formed an oil-in-water Pickering emulsion with an average droplet size of 5.54 µm. The emulsion-added films led to significant inhibition of microbial growth of E. coli, S. aureus, and B. cinerea . Moreover, there was no significant adverse effect on the films' mechanical properties, water vapor permeability, or solubility with 1% and 2% emulsions added. Lastly, the antimicrobial films with 2% emulsion inhibited the deterioration rate of strawberries by 52.2%. The CNC-LAE-cinnamaldehyde Pickering emulsions-added films demonstrate a promising application for antimicrobial food packagings. Highlights: Cationic LAE used to modify CNC surface and tailor packing density at o/w interface. LAE modified CNC improved the stability and uniformity of cinnamaldehyde emulsion. Emulsion incorporated films showed remarkable antibacterial and antifungal activity.